A atual reforma trabalhista: Possibilidades, problemas e contradiç\~oes - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Since the 1930s, the Brazilian State has built a national system of labour relations. In the following decades, this system underwent many changes, as well the country itself (which became urbanized, industrialized etc.). At the present time, there is a new wave of changes in the labour relations system - which will be analyzed, in this article, only in its aspects more directly related to the work realm. This new wave, initiated with a set of legislative proposals, will alter the balance between workers' protections and freedoms of employers. Assuming the perspective of the former, this article analyzes the possibilities opened by Law no 13.467/2017 (recently approved), as well as its problems and contradictions.
Keywords: J00; J50; J80; 330; labor relations; workers; employers